Development and validity test of impression management efficacy scale based on self-presentation behavior of Chinese youth on social media - Yixuan Liu; Ke Lei (Frontiers in Psychology)
IntroductionThis study seeks to develop and validate a scale for assessing Impression Management Efficacy (IME) in the context of Chinese youth’s self-presentation behaviors on social media. It aims to provide a comprehensive evaluation of their ability and self-efficacy in managing impressions within social media environments.MethodsFor this study, 18 young individuals were selected to participate in in-depth interviews. The specific dimensions of IME were identified through the application of grounded theory categorization. Subsequently, specific measurement questions were formulated by referencing the impression management scale, the social self-efficacy scale, and insights from empirical interviews, leading to the preliminary compilation of the questionnaire. A total of 920 questionnaires were then distributed for a centralized investigation. The collected data underwent repeated testing to refine and finalize the questionnaire.ResultsThis study explores the relationship between self-presentation and IME in social media contexts. Through multiple tests and empirical data analysis, IME was delineated into five distinct dimensions: identity management strategy, self-impression management strategy, communication expression efficacy, protection strategy efficacy, and self-presentation efficacy, collectively encompassing 25 measurement items. The study is inherently exploratory in nature.DiscussionThe concept of IME among young people is distinct yet related to traditional notions of impression management and social self-efficacy. While impression management primarily focuses on external behaviors, social self-efficacy assesses one’s perceived social abilities. Both concepts, along with their measurement methods, tend to be relatively singular in focus. IME, however, is closely intertwined with these concepts but possesses a unique conceptual depth and theoretical significance, setting it apart as a multifaceted and nuanced construct.